Crisis Management in Islamic Boarding Schools: Radicalism Issues and Negative Perceptions - Abidin, Zainal; Qusairi, Ahmad (Universitas Islam Negeri Walisongo, 2025)
Islamic boarding schools (pesantren) in Indonesia are pivotal in shaping character and promoting religious moderation but face challenges such as radicalism, negative perceptions, and communication conflicts. These issues can lead to crises including social tension, degraded image, internal disintegration, and threats to sustainability. This study investigates the crisis management strategies of pesantren, focusing on factors enabling and hindering success. The research employs a qualitative approach, using an interpretive paradigm to conduct in-depth interviews with 25 informants from four pesantren in East Java, supported by direct observation and document analysis. Thematic analysis reveals that effective crisis management hinges on communication readiness, fostering tolerance and moderation, and strategic collaboration with external entities like security forces and community leaders. Pesantren that swiftly respond and cultivate positive narratives through strategic communication, underpinned by a strong internal culture, better mitigate radicalism's effects and enhance their moderate image. These insights underscore the necessity of a holistic crisis management strategy to ensure the stability and sustainability of pesantren in society.